Improving SVDD classification performance on hyperspectral images via correlation based ensemble technique - Uslu, Faruk Sukru; Binol, Hamidullah; Ilarslan, Mustafa; Bal, Abdullah (ELSEVIER SCI LTD, 2017)
Support Vector Data Description (SVDD) is a nonparametric and powerful method for target detection and classification. The SVDD constructs a minimum hypersphere enclosing the target objects as much as possible. It has advantages of sparsity, good generalization and using kernel machines. In many studies, different methods have been offered in order to improve the performance of the SVDD. In this paper, we have presented ensemble methods to improve classification performance of the SVDD in remotely sensed hyperspectral imagery (HSI) data. Among various ensemble approaches we have selected bagging technique for training data set with different combinations. As a novel technique for weighting we have proposed a correlation based weight coefficients assignment. In this technique, correlation between each bagged classifier is calculated to give coefficients to weighted combinators. To verify the improvement performance, two hyperspectral images are processed for classification purpose. The obtained results show that the ensemble SVDD has been found to be significantly better than conventional SVDD in terms of classification accuracy. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Classification; Data fusion; Ensemble method; Hyperspectral images; Support Vector Data Description; SUPPORT; FEATURES; Optics